Surgical management of tailgut cysts: A rare case report. Issue 6 (February 2019) - Li, Jiannan; Song, Xiaowei; Shi, Jian; Zhang, Kai; Liu, Tongjun
Abstract: Rationale: Tailgut cysts are a type of very rare congenital polycystic lesions that are always located posterior to the rectum and anterior to the sacrum. The symptoms of tailgut cysts are nonspecific and misleading. Therefore, a full understanding of the characteristics of tailgut cysts is important for their diagnosis and treatment. Patient concerns: We report a 46-year-old female with a sacrococcygeal mass that had been present for about 2 years. Diagnoses: Pelvic magnetic resonance imaging (MRI) indicated several cystic masses, the largest of which had a diameter of about 2.8 cm, near the ligaments of the sacrospinous and rectum. Pathological examination confirmed the tailgut cysts, with no signs of malignant transformation. Interventions: The patient received complete surgical cysts resection, which was performed through the sacrococcygeal region. Outcomes: The patient recovered well with no obvious complication and was discharged on the sixth-day post-surgery. Follow-up 6 months later revealed no signs of cyst recurrence. Lessons: The symptoms and diagnostic characteristics of tailgut cysts should be fully understood. Complete surgical resection through the sacrococcygeal region is vital to treat tailgut cysts.